A taxa de referência e o seu impacto na inflação, na taxa de juro e na taxa de câmbio num contexto global - Gomero Gonzales, Nicko Alberto (2024)
Objective: Demostrar la incidencia de la tasa de referencia sobre la inflación, la tasa de interés y el tipo de cambio. Methods: This study employed a quantitative and explanatory approach. Data was sourced from official institutions such as the Central Reserve Bank of Peru (BCRP), the Federal Reserve (FED), and the World Bank. Each test conducted using EViews 10 and the respective hypotheses were formulated. Results: The analysis revealed an inverse and highly significant relationship between the FED reference rate and US inflation, a correlation not observed in the Peruvian economy where the relationship between the two variables is inverse but not significantly so. Likewise, it was demonstrated that the reference rate managed by the BCRP is influenced by the FED rate, indicating these measures are standard procedures to combat price volatility and maintain the stability of the exchange market due to the level of dollarization of the economy. The financial cost of large companies was found to be sensitive to the interest rates established by Central Banks. Conclusion: The reference rate is an instrument to stabilize the prices of the economy and generate influence in the financial costs of the companies.